Geochemical and Crystallographic Study of Turbo Torquatus (Mollusca: Gastropoda) From Southwestern Australia - Roger, L.; George, A.; Shaw, J.; Hart, R.; Roberts, M.; Becker, T.; Evans, Noreen; Mcdonald, B. (Wiley-Blackwell Publishing, 2018)
© 2017. American Geophysical Union. All Rights Reserved. Shells of the marine gastropod Turbo torquatus were sampled from three different locations along the Western Australian coastline, namely Marmion Lagoon (31°S), Rottnest Island (32°S), and Hamelin Bay (34°S). Marmion Lagoon and Rottnest Island have similar sea surface temperature ranges that are ~1°C warmer than Hamelin Bay, with all sites influenced by the warm southward flowing Leeuwin Current. The shells were characterized using crystallographic, spectroscopic, and geochemical analyses. Shell mineral composition varies between the three sites suggesting the influence of sea surface temperature, oxygen consumption, and/or bedrock composition on shell mineralogy and preferential incorporation and/or elemental discrimination of Mg, P, and S. Furthermore, T. torquatus was found to exert control over the incorporation of most, if not all, the elements measured here, suggesting strong biological regulation. At all levels of testing, the concentrations of Li varied significantly, which indicates that this trace element may not be a suitable environmental proxy. Variation in Sr concentration between sites and between specimens reflects combined environmental and biological controls suggesting that Sr/Ca ratios in T. torquatus cannot be used to estimate sea surface temperature without experimentally accounting for metabolic and growth effects. The mineral composition and microstructure of T. torquatus shells may help identify sea surface temperature variations on geological time scales. These findings support the previously hypothesized involvement of an active selective pathway across the calcifying mantle of T. torquatus for most, if not all, the elements measured here.